(3efJgi GdebGd aj CMhGd GdQLGds - (3GdeGRfOQGfj, GdMGFQj, CHh Ydj, eMeO Hf ESeGYjd Hf YHO GdLHGQ GdeGRfOQGfj GdMGFQj, J (B1215(3g` (B1800(3es
(3ChdgG (B:s
(3ChdgG(B: (3fMeOc jG ef QaY efGRd GdQhGI HbOQ eG jMSfhf ef GdQhGjI Yf GdCFeI GdgOGI (B... (3GdebOeI GdChdi aj JGQjN ehGdjO GdCFeI hhajGJge aEf GdfGXQ aj gPG GdYde dG HO dg ef YQaGfgs
(3BNQgG (B:s
(3BNQgG(B: (3hEdi CMeO Hf eMeO Hf SYjO GdgeOGfj ajg eMeO Hf EHQGgje Hf ESMGb GdWGdbGfj hdG CYde NGdO (B... (3GdUOhb Yfg eQVjG heJQMeG hgPG QHeG CTgQ efg Hchfg eQVjG YfOgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdPQjYI, L (B23: 9s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3GdJGQjNs